A Case of Balloon Rupture Cause Serious Complication during Percutaneous Coronary Intervention - Jianan Li; Shuzheng Lyu; Fei Yuan; Rui Tian; Xiantao Song (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Balloon rupture in the process of percutaneous coronary intervention (PCI) leading to coronary artery dissection, subintimal hematoma and hematoma extension after stent implantation is an uncommon complication, but it has important clinical signifi cance. The reason for balloon rupture during PCI and hematoma extension after stent implantation is not clear. In this case, Balloon rupture may be due to excessive balloon dilation pressure, severe coronary artery calcifi cation, balloon dilatation with gas presence and poor quality of the balloon; hematoma extension after stent implantation may be for remaining undiscovered hematoma and dissection. We should pay attention to these risk factors and prevent the occurrence of clinical complications in the treatment of PCI.